Proposed interior design scheme of animal welfare centre for SPCA at No 25, Jalan Sultan Ismail, 50250 Kuala Lumpur / Nurlina Khairuddin - Khairuddin, Nurlina (Faculty of Architecture, Planning and Surveying, 2011)
Nowadays, in Malaysia, consideration regarding animal welfare is widening. Animal welfare is not just the physical and psychological term but more adapted to lifestyle. However, the infrastructure for the community especially to animal lovers to their interest is not a great deal. Competitive environment in pet centre or pet shop is getting more intense. Animal welfare is not just about commercializing the animal but to fight for their rights. Therefore, such infrastructure is needed in order to provide education on animal care. Hence, a new iconic eco-green SPCA Animal Welfare Centre at Jalan Sultan Ismail, Kuala Lumpur has been proposed. The aim is to introduce the community to a green design animal centre in Malaysia. It will be a new culture in animal welfare in Malaysia where animal welfare and pet centre is intertwined. Design concept and implementation will act as profoundest study. All the data and details that been collected from research and observation conducted, was use as a parameter in the design process.